The Effect of Story Map To Reading Comprehension of Narrative Text Ability at The X Grade of SMA Negeri 5 Padangsidimpuan - Jenni Artika (Institute of Information Technology and Social Science (IITSS), 2020)
The aim of this research was to fid out whether there is any significant effect of story map to reading comprehension of narrative text ability at the X grade of SMA Negeri 5 Padangsidimpuan. The experimental research method was used to conduct this research. The population was tended to students in the grade X of SMA Negeri 5 Padangsidimpuan with 175 students. The sample was taken by using cluster sampling and it tended to the X-3 grade of SMA Negeri 5 Padangsidimpuan with 33 students. Test and observation were used to collect data. In analysis, the writer took descriptive and statistic analyzes by using t-test formula to know interpretation of data. Based on the descriptive analysis, the writer got the students got enough category in reading comprehension of narrative text ability without using story map to get comprehension with 60.00 average. Then the students enough category after using story map to get comprehension with 67.72 averages. In the statistic analysis, tcount was higher than ttable or 4.41 > 2.75. It meant the hypothesis alternative was accepted. Therefore, there was significant effect of story map toward reading comprehension of narrative text ability at the X grade of SMA Negeri 5 Padangsidimpuan